Blast mitigation performance of cladding using square dome-shape kirigami folded structure as core - Li, Z.; Chen, Wensu; Hao, Hong (Pergamon, 2018)
Structural response of the sacrificial cladding with square dome-shape kirigami (SDK) structure as core under blast loads is investigated in this study. A sample of SDK core folded from a pre-cut aluminium sheet is crushed under quasi-static loading condition. A numerical model is then developed and calibrated using experimental data. The calibrated model of SDK foldcore cladding is then placed on to a rigid block as a sacrificial layer to resist blast loading for structure protection. To evaluate the blast mitigation capacities, the parameters such as peak load transmitted to the protected structure, energy absorption, centre crushed distance and loading duration are compared among the claddings with different cores. Compared to square honeycomb, superior performance of blast mitigation is demonstrated for the proposed SDK foldcore sacrificial cladding by yielding a uniform collapsing similar to aluminium foam. Significant increase in energy absorption of the core is observed for the sacrificial cladding with SDK foldcore. It also yields a higher plateau stress than aluminium foam of the same density and is applicable to a wider range of blast loadings. The peak transmitted load to the protected structure is reduced by more than 70% comparing with the case without cladding. SDOF analysis of the sacrificial cladding systems is carried out and validated using numerical results. Based on the SDOF analysis, complete solution is derived and then used to obtain simplified design charts to show the suitable range of blast load scenarios where the sacrificial claddings are effective.